Comparison of garden pavilions’ site selection in China and Italy - Liu, Ning; Fabris, Luca Maria Francesco; Fu, Fan; Wang, Jingyao (Landscape Architecture and Art, 2025)
This study examines Chinese and Italian garden pavilions through a comparative approach, systematically exploring the similarities and differences in their site selection and the underlying cultural motivations. Chinese garden pavilions are profoundly shaped by the philosophy of “the unity of man and nature,” emphasising harmony with natural landscapes and adaptable layouts. Techniques such as situating pavilions by mountains and water bodies are employed to achieve an organic integration of architecture and environment. In contrast, Italian pavilions embody geometric order and rational aesthetics, characterised by axial symmetry and the deliberate terrain modification to shape structured spatial sequences. Through an analysis of philosophical concepts, locational characteristics, and spatial organisation, the research reveals both the commonalities and differences in the siting of pavilions on elevated grounds, by water, on flat terrain, and in compositional groupings, while providing an in-depth examination of their relationships with topography, water features, vegetation, and other architectural structures.